Eternal truths and Cartesian circularity - Mawson, T (Taylor and Francis, 2001)
'Voluntarism casts no useful light on those aspects of the Meditations that have received the most attention: the truth rule, divine veracity, the relation between those, the Cartesian Circle' (Bennett). In this paper, I shall draw together various strands from recent Descartes scholarship to argue that this is entirely false. When Descartes' voluntarism is understood as central to his epistemological project, not only does it allow us to make more sense of what he says on all these issues, but also it allows us to see what he says, on certain assumptions, unassailable. The only difficulty that then remains is that these assumptions are widely held to be necessarily false.